The influence of Cu content on microstructure and mechanical properties of PM-fabricated Ti-18Nb-xCu alloy - Demirtaş, Hüseyin; Anaee , Rana Afif; Faaik , Muhamad Saad (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
This research investigated the influence of varying copper (Cu) concentrations (0, 5, 7, and 9 wt.%)on the sintering behaviour, microstructural development, and mechanical characteristics of Ti-18Nb alloy, fabricated through conventional powder metallurgy. Under specific sintering conditions (1150°C for 5 hours), Cu addition led to a more homogeneous microstructure and promoted the complete dissolution of Nb particles. X-ray diffraction (XRD) analysis confirmed the presence of alpha (α) and beta (β) Ti phases, along with the Ti2Cu phase, with its peak intensity increasing as Cu content rose. Mechanical properties were significantly enhanced by Cu addition. Yield strength increased almost linearly with Cu content. Compressive strength notably increased with 7 wt.% Cu, reaching 980 MPa, and slightly exceeded this value with 9 wt.% Cu. Hardness values increased due to solid solution strengthening in the α-Ti phase and the precipitation of the Ti2Cu phase, with the highest hardness (222 HV) observed in the 7 wt.% Cu alloy. The elastic modulus initially increased with 5 wt.% Cu, then subsequently decreased with further Cu additions; the Ti-18Nb-7Cu alloy exhibited the lowest elastic modulus at 13.34 GPa. Furthermore, the resilience of the alloys improved with the formation of the Ti2Cu phase, and a maximum value of 13.15 MJ m−3 was achieved.